A Feminist Approach to Teaching Women's Issues in Counsellor Education - Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Methodologies used in a graduate course on women's issues in counselling are described and implications for counsellor education are discussed. Emphasis is placed on including experiential learning activities to help students better understand women's experiences within this culture. The didactic section of the course focuses on counselling concepts and interventions for dealing with the many issues that women bring to counselling.